THE ROLE OF INTERNAL COMMUNICATION IN DRIVING EMPLOYEE ENGAGEMENT (STUDY CASE OF PT. SINAR GALESONG PRIMA MANADO) - Pungus, Jeaneta Sarah; Saerang, David P. E.; Pandowo, Merinda . (Universitas Sam Ratulangi, 2017)
Abstract: The rise of globalization developments in economic, political, social, areas crucially affects organizational lives of individuals in the society. With these developments organization management are obliged to develop new management to struggle the competition conditions. The purpose of this research is to know how is the role of internal communication in driving PT. Sinar Galesong Prima employee engagement. This research is qualitative analysis interview, the population is the employee of PT. Sinar Galesong Prima, and the sample method is using snowball sampling. The data were gathered through interview with informants and examination of the literature review from previous researcher. The result is all the informants explained that the role of internal communication is very important in driving employee engagement. The conclusion is Employees at PT. Sinar Galesong Prima think that Internal Communication is important, formally and informally. The communication media that being used situation ally is Direct Communication and Telecommunication such as Messaging App, and regarding employee engagement, PT. Sinar Galesong Prima manage to make their employee engaged by giving bonus, and also gives personal compliments to employee. This research recommend PT. Sinar Galesong Prima to teach their employee to always using formal communication in routine to increase their employee engagement.Keywords: internal communication, employee engagement.